Pluralistic extension system in Malawi - Masangano, Charles; Mthinda, Catherine (International Food Policy Research Institute, 2012)
This descriptive study was undertaken in order to assess the status of extension services in Malawi 10 years after implementation of the pluralistic and demand-driven extension policy. The findings would help practitioners and policy makers in their efforts to strengthen the extension system and enable it to serve the smallholder farmers more effectively. A worldwide extension assessment mail-out questionnaire was administered to 37 agricultural extension service providers to collect quantitative data on primary organizational goals, functions, and resources, and the linkages of different extension organizations within an agricultural innovation systems framework. The findings indicate that there were many players in agricultural extension service delivery as a result of the pluralistic policy but the government extension service remained the largest in terms of staffing and spread. The primary focus for most organizations was to help smallholder farmers improve their livelihoods with special efforts to target women. Government extension service was characterized by limited resources, but many field staff with low qualifications. Most of the other extension organizations had limited staff concentrated at higher levels with no grassroots staff thereby depending on government extension staff to reach farmers. Strong institutional linkages existed at district levels and local agencies as well as with non-governmental organizations but there were weak linkages with education and research institutions. Among others, the study calls for more investments in the government extension system while strengthening coordination with the civil society organizations to effectively serve the needs of smallholder farmers in Malawi.